التدفق النفسي وعلاقته بالكفاءة الذاتية لد ى مد ا رء الثانويات بولاية الواد ي - حنكة, جهينة; بوغزالة محمد, خلود (جامعة الوادي - University of Eloued, 2022)
تهدف الدراسة الحالية إلى التعرف على علاقة التدفق النفسي بالكفاءة الذاتية لدى مدراء الثانويات بولاية الوادي، وللتأكد من صحة فرضيات الدراسة تم استخدام مقياسين وهما مقياس التدفق النفسي لجاكسون ومارش 1996ومقياس الكفاءة الذاتية لعادل العدل2001 وبعد التأكد من الخصائص السيكومترية ،تم تطبيقهما على عينة تكونت من (48) مديرا، وقد تحددت الدراسة بالمنهج الوصفي الارتباطي، وبعد جمع البيانات وتفريغها، تمت المعالجة الإحصائية باستخدام البرنامج الإحصائي للعلوم الاجتماعية أسبياس . وقد أسفرت نتائج الدراسة على ما يلي: - توجد علاقة ارتباطية دالة إحصائيا عند مستوى الدلالة( ) بين التدفق النفسي والكفاءة الذاتية لدى مدراء الثانويات. - لا توجد فروق دالة إحصائيا عند مستوى الدلالة ( ) بين مدراء الثانويات على مقياس التدفق النفسي تبعا للعمر(40 سنة فأقل/أكثر من40 سنة). - لا توجد فروق دالة إحصائيا عند مستوى الدلالة ( ) بين مدراء الثانويات على مقياس الكفاءة الذاتية تبعا للعمر(40 سنة فأقل/أكثر من40 سنة). - لا توجد فروق دالة إحصائيا عند مستوى الدلالة ( ) بين مدراء الثانويات على مقياس التدفق النفسي تبعا للأقدمية(5سنوات فأقل/أكثر من5 سنوات). - توجد فروق دالة إحصائيا عند مستوى الدلالة ( ) بين مدراء الثانويات على مقياس الكفاءة الذاتية تبعا للأقدمية(5سنوات فأقل/أكثرمن5 سنوات).وفي الأخير تمت مناقشة وتفسير النتائج وفق التراث النظري في الموضوع, والدراسات السابقة وبناءا على ذلك تم تقديم توصيات ومقترحات. The current study aims to identify the relationship of psychological flow to self-efficacy among high school principals in El-Wadi State. ) Director, and the study was determined by the descriptive correlational approach, and after data collection and unloading, the statistical treatment was carried out using the statistical program for social sciences (SPSS). The results of the study resulted in the following: - There is a statistically significant correlation at the level of significance ( ) between psychological flow and self-efficacy among secondary school principals. - There are no statistically significant differences at the level of significance ( ) between secondary school principals on the psychological flow scale according to age (40 years and less/more than 40 years). - There are no statistically significant differences at the level of significance ( ) between secondary school principals on the self-efficacy scale according to age (40 years and less/more than 40 years). - There are no statistically significant differences at the level of significance ( ) between secondary school principals on the psychological flow scale according to seniority (5 years and less / more than 5 years). - There are statistically significant differences at the level of significance ( ) between secondary school principals on the self-efficacy scale according to seniority (5 years and less / more than 5 years). Finally, the results were discussed and interpreted according to the theoretical heritage in the subject, and previous studies were based on that, recommendations and suggestions were presented
مذكرة ماستر علم النفس مدرسي
Keywords: التدفق النفسي ،الكفاءة الذاتية ، مدراء الثانويات ،الوادي; Psychological flow , self-efficiency , high school principals ,El-Oued